Rostov-on-Don anti-plague institute — 85 years is on guard for epidemiological well-being of the country - S. V. Titova; I. A. Schipeleva; E. I. Markovskaya; О. F. Kretenchuk; О. S. Chemisova; L. P. Alekseeva (Медицинский вестник Юга России, 2019)
In 2019 Rostov-on-Don anti-plague institute celebrates its 85th anniversary since it was founded. The article represents information about the development of the anti-plague service in southern Russia, since 1912. Here we describe the main milestones in the institute development during the period from 1934 year until now. The article indicates primary global tasks for highly infectious disease control, which were assigned on the institute by the establishment of the country. The article is concerned with the most significant achievements in epidemiological surveillance of the country well-being, that were reached by the scientists of the institute.